Evaluating N2O5 heterogeneous hydrolysis parameterizations for CalNex 2010. Issue 9 (7th May 2016) - Chang, Wayne L.; Brown, Steven S.; Stutz, Jochen; Middlebrook, Ann M.; Bahreini, Roya; Wagner, Nicholas L.; Dubé, William P.; Pollack, Ilana B.; Ryerson, Thomas B.; Riemer, Nicole
Abstract: Nighttime chemistry in the troposphere is closely tied to the dinitrogen pentoxide (N2 O5 ) budget, but high uncertainties remain regarding the model representation of the heterogeneous hydrolysis of N2 O5 on aerosol particles. In this study we used the community model WRF‐Chem to simulate a 3‐day period during the California Nexus (CalNex) Campaign in 2010. We extended WRF‐Chem to include the heterogeneous hydrolysis of N2 O5 and contrasted the impact of different published parameterizations of N2 O5 heterogeneous hydrolysis on the spatial distribution of uptake coefficients and the resulting N2 O5 concentrations. For all the cases, modeled N2 O5 uptake coefficients showed strong spatial variability, with higher values in the nocturnal boundary layer compared to the residual layer, especially in environments with high relative humidities, such as over the ocean and along the coast. The best agreement of modeled and observed uptake coefficients was obtained using the parameterization by Davis et al. (2008) combined with the treatment of organic coating by Riemer et al. (2009). For this case the temporal evolution of lower boundary layer N2 O5 mixing ratios was reproduced well, and the predictions of surface mixing ratios of ozone and NO x were improved. However, the model still overpredicted the uptake coefficients in the residual layer and consequently underpredicted N2 O5 concentrations in the residual layer. This study also highlights that environments with low relative humidities pose a challenge for aerosol thermodynamic models in calculating aerosol water uptake, and this impacts N2 O5 heterogeneous hydrolysis parameterizations. Key Points: Evaluated parameterizations of N2 O5 heterogeneous hydrolysis for CalNex 2010 using WRF‐Chem N2 O5 uptake coefficient parameterization has noticeable impact on NO x and ozone predictions Improved closure for modeled and observed uptake coefficients when including organic coatings